Highly enantioselective copper-catalyzed electrophilic trifluoromethylation of β-ketoesters - Deng, Qing-Hai; Wadepohl, Hubert; Gade, Lutz H. (Journal of the American Chemical Society, 2012)
Enantioselective Cu-catalyzed triﬂuoromethylation of β-ketoesters using commercially available triﬂuoromethylating reagents is reported. A number of αCF3 β-ketoesters are obtained with up to 99% ee. The triﬂuoromethylated products were then transformed diastereoselectively to α-CF3 β-hydroxyesters with two adjacent quaternary stereocenters via a Grignard reaction.